Effects of dietary Acremonium terricola culture on production performance, serum biochemical parameters, egg quality and yolk amino acid contents of Beijing You-chicken - Wang, Jianzhong; Liu, Cun; Gong, Xiaowei; Liu, Yanhan (BMC veterinary research, 2025)
The effects of Acremonium terricola culture (ATC) on production performance, serum biochemical parameters, egg quality and amino acid contents in the yolk of eggs of Beijing You-chicken were conducted in the current study. A total of 216 Beijing You-chickens (330 days old) were randomly divided into 2 groups. The control group (CON) was fed a corn-soybean-based diet, and the experimental group was fed a basal diet supplemented with 0.20% ATC. The pretest period was 7 d, and the experiment period was 8 weeks. The production performance, serum biochemical parameters, egg quality, and the concentrations of amino acids in the yolk of eggs were measured at the 4 weeks (FW, the first stage) and the 8 weeks (EW, the second stage) of the experiment, respectively. Compared with the CON group, there were no significant differences (P > 0.05) in the production performance of the experimental group at the end of four- and eight-week periods of study. The concentration of serum LH, FSH and E2 increased significantly for the ATC group, at both time periods when compared to CON group, while the triglyceride (TG) content was only increased significantly (P < 0.05) in the first stage. The average egg weight, albumen height, and Haugh unit representing egg quality of Beijing You-chickens in the experimental group were increased significantly (P < 0.05) compared with the CON group at both time periods, while the egg shape index and yolk weight were only increased significantly (P < 0.05) in the second stage. The protein content in the yolk was increased significantly at both time periods (P < 0.05). Levels of lecithin and Vitamin A in yolks of the ATC supplemented group increased significantly (P < 0.05) compared to the CON group, at both FW and EW, respectively. The contents of aspartic acid, threonine, methionine, leucine, and arginine were increased significantly in the first stage. In addition, the contents of threonine, glutamine, and valine were increased significantly in the second stage (P < 0.05). Our results suggest that dietary supplementation with 0.20% ATC improves serum biochemical parameters and egg quality in Beijing You-chickens. Future studies should focus on optimizing ATC dosage and exploring its underlying mechanisms for enhanced poultry production.